The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1111/nhs.12537
|View full text |Cite
|
Sign up to set email alerts
|

Decisional conflict in end‐of‐life cancer treatment among family surrogates: A cross‐sectional survey

Abstract: The aims of this study were to examine the extent of decisional conflict in end-of-life cancer treatments and to investigate the influences and predictors of decisional conflict among family surrogates. A cross-sectional, descriptive, correlational design was applied. Data were collected from a convenience sample of 102 family members who had participated in end-of-life cancer decision-making. We enrolled participants from inpatient oncology units at a university hospital in South Korea from May 2014 to Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
1
10
1
Order By: Relevance
“…This high prevalence contrasts with the literature consensus that a minority of individuals experience heightened decisional regret when they make decisions (primarily not EOL‐care decisions) for themselves 9 or others 11,16,34 . Our participants' decisional regret may be more comparable to that of Korean surrogates who decided about forgoing life‐sustaining treatments for their relative (mean = 45.4) 10 . We also observed that surrogates' likelihood of heightened decisional regret increased as their relative's death approached (Table 3).…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…This high prevalence contrasts with the literature consensus that a minority of individuals experience heightened decisional regret when they make decisions (primarily not EOL‐care decisions) for themselves 9 or others 11,16,34 . Our participants' decisional regret may be more comparable to that of Korean surrogates who decided about forgoing life‐sustaining treatments for their relative (mean = 45.4) 10 . We also observed that surrogates' likelihood of heightened decisional regret increased as their relative's death approached (Table 3).…”
Section: Discussioncontrasting
confidence: 84%
“…Our participants' decisional conflict level is substantially higher than those of US surrogates making EOL‐care decisions (mean DCS scores ranged 21.5–25.5 30,34,35 ) but is comparable with those reported among international patients and surrogates making palliative‐care decisions (mean = 45.0) 5 . However, our participants' mean was markedly lower than that for Korean surrogates who decided to forgo their relative's life‐sustaining treatments (mean = 56.3, n = 102), 10 a rare decision in our study (4.1%, Supporting Information S1: Table 1). Deciding to withdraw/withhold life‐sustaining treatments is extremely difficult for Asian families due to the strong cultural, Confucian influence of filial duty 4 to use every means to keep a relative alive.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Although the physician-patients were more informed than most lay patients about their illness, prognosis and treatment options and their family caregivers were also well educated, family caregivers reported concerns that have been reported among lay family caregivers. For example, family caregivers talked about their desire to reach consensus with other family members on treatment and care decisions for the physician patient but recognized that some level of conflict among the family members might occur [33]. Similar to other studies of caregivers of persons with serious illness, faith beliefs and religious practices provided great comfort to some of the family members of the physician-patients especially near death, but divergent beliefs created conflict [34].…”
Section: Discussionmentioning
confidence: 88%